ASSESSMENT OF THE CONTRIBUTION OF PUBLIC-PRIVATE MIX INITIATIVE ON DETECTING TUBERCULOSIS PATIENTS NATIONWIDE DURING THE PERIOD 2021-2023 (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the contribution of public-private mix initiative on tuberculosis case-finding in Viet Nam, in the period 2021-2023.Subjects and methods: A retrospective descriptive study using secondary data aggregated from the VITIMES system and routine reports of the National Tuberculosis Program. Indicators included the number of participating health facilities, operational models, and the proportion of tuberculosis patients detected through the public-private mix system. Data were analyzed using Excel and SPSS 27 software; proportions were calculated and trends were tested using Cuzick’s test (p < 0.05). The study complied with National Tuberculosis Program regulations on the use of secondary data and general ethical requirements for secondary data use.Results: The number of health facilities participating in public-private mix increased from 39.150 (in 2021) to 43.534 (in 2023). Most facilities participated under model 1 (referral of presumptive tuberculosis cases), accounting for 96.1% in 2023. The proportion of tuberculosis patients detected through the public-private mix system among all notified tuberculosis cases nationwide increased from 19.8% (in 2021) to 32.1% (in 2023), showing a statistically significant upward trend (p < 0.001).Conclusion: Public-private mix activities have made an increasingly important contribution to tuberculosis case detection in Vietnam during 2021-2023. Strengthening and scaling up effective public-private mix models, ensuring technical support and data sharing, and maintaining local implementation capacity are essential to sustain this progress toward ending tuberculosis by 2030.
Keywords: Tuberculosis, public-private mix, case-finding.